J. Mikulicz-Radecki, K. H. Bauer, and W. Bross. Three Great Surgeons, Three Different Epochs, One Clinic in Wroclaw - Kustrzycki, Wojciech Anatol (The Thoracic and Cardiovascular Surgeon, 2013)
The city of Wroclaw (Breslau) lies where the cultural and economic influences of the eastern, southern, and western Europe meet. Over a thousand years of history it changed the state affiliation several times. Since 1945, similarly as seven centuries ago, it lies within the borders of Poland. The historical complex of hospital buildings constructed at the end of the 19th century for the medical faculty remained almost untouched, despite catastrophic war destructions in the whole city. The building of surgical clinic witnessed epoch-making events in the discipline of surgery performed by the three great personalities. Jan Mikulicz-Radecki (1850–1905), the first head of the department, world famous physician and scientist, created in Wroclaw a modern surgical center. From among his numerous achievements the most important seems to be the performance of the world's first safe thoracotomy in the low-pressure chamber (1904). Karl Heinrich Bauer (1890–1979) was the next great personality, who had been leading the surgical department since 1933. Genetics, transplantology, traumatology and oncology were the main points of his interest. Because of political reasons he had to leave Wroclaw. He continued his surgical and scientific career in Heidelberg. Wiktor Bross (1903–1994) came to the ruined city directly after the World War II. As an experienced general and thoracic surgeon he created a new surgical school. First in Poland open heart surgery (1958) and renal transplantation (1966) were performed by him and his team in the same building, where Mikulicz-Radecki and Bauer worked in the past. The memory of all three great surgeons has been honored by placing their sculptures among the prominent Wroclaw citizens in the city hall.
Keywords: history; cardiac surgery; thoracic surgery